2016
DOI: 10.1590/1807-3107bor-2016.vol30.0070
|View full text |Cite
|
Sign up to set email alerts
|

Maternal care influence on children’s caries prevalence in southern Brazil

Abstract: This study aimed to investigate the influence of specific maternal-factors on caries prevalence in offspring. This cross sectional study was conducted in Pelotas, Brazil nested in a cohort of adolescent mothers with children aged 24-42 months. A questionnaire was administered to collect information in relationship to socio-economic, demographic, and behavioral maternal variables. The outcome (children's dental caries prevalence -dmfs > 0) was collected from clinical examinations. Bivariate and multivariate ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 24 publications
1
16
0
1
Order By: Relevance
“…Some authors found that small children living in single-parent families are less likely to pay preventative visits to their dentist [10] and tend to have more tooth decay compared to two-parent families [10]. Families headed by single mothers are even more vulnerable [34]. The findings in this study are in agreement with that, given that families whose mothers are raising their children on their own presented with higher prevalence of visible bacterial plaque, an etiological factor of early childhood caries.…”
Section: Discussionsupporting
confidence: 88%
“…Some authors found that small children living in single-parent families are less likely to pay preventative visits to their dentist [10] and tend to have more tooth decay compared to two-parent families [10]. Families headed by single mothers are even more vulnerable [34]. The findings in this study are in agreement with that, given that families whose mothers are raising their children on their own presented with higher prevalence of visible bacterial plaque, an etiological factor of early childhood caries.…”
Section: Discussionsupporting
confidence: 88%
“…The avoidance of dental treatment by mothers creates a worse scenario for their children´s oral health (20). Indeed, a recent study observed that maternal oral health practices from mothers were associated to children's caries prevalence and also that mothers could accurately evaluate their children's oral health (21).…”
Section: Discussionmentioning
confidence: 99%
“…The question was developed based on the questions of previous studies evaluating mother perception of child's oral health. 22,23 The parents/caregivers also answered the Portugueselanguage validated version of the Sleep Disturbance Scale for Children (SDSC). 24,25 The instrument is composed by 26 multiple-choice questions divided into six domains (six groups of the most common types of sleep disorders in children and adolescents): disorders of initiating and maintaining sleep (DIMS); sleep breathing disorders (SBD); disorders of arousal (sleepwalking, sleep terrors, nightmares) (DA); sleep-wake transition disorders (hypnic jerks, rhythmic movement disorders, hypnagogic hallucinations, nocturnal hyperkinesia, bruxism) (SWTD); disorders of excessive somnolence (DOES); and sleep hyperhidrosis (SHY).…”
Section: Data Collectionmentioning
confidence: 99%